Olfactory Dysfunction and Asthma as Risk Factors for Poor Quality of Life in Upper Airway Diseases. Issue 4 (July 2013) - Katotomichelakis, Michael; Simopoulos, Efthimios; Zhang, Nan; Tripsianis, Gregory; Danielides, Gerasimos; Livaditis, Miltos; Bachert, Claus; Danielides, Vassilios
Background: The study of olfaction/quality of life (QoL) interaction has not been adequately discussed and remains to be further explored. Determination of clinical predictors for poor QoL may support consultation of respective patients. This study explores QoL of patients with olfactory dysfunction and evaluates associated clinical risk factors for QoL prediction. Methods: One hundred eight patients suffering from chronic rhinosinusitis (CRS) and allergic rhinitis (AR) and 30 healthy subjects were studied. Olfactory function was evaluated using objective olfactory test. All patients completed six validated questionnaires either specific for olfaction (Questionnaire of Olfactory Deficits [QOD]) and for assessing psychological state (Zung Anxiety Scale [ZAS], State-Trait Anxiety Inventory, Zung Depression Scale, and Beck Depression Inventory [BDI]) or a generic one (Short Form 36). Results: Significantly poorer QoL and more severe anxiety and depression symptoms were observed in anosmic (all p < 0.001) and hyposmic patients compared with controls. Anosmic patients presented significantly worse results compared with hyposmic and normosmic patients. However, higher scores were observed in hyposmic compared with normosmic patients only in the QOD, ZAS, and BDI scale. Patients with CRS presented significantly poorer QoL than patients with AR only. The presence of nasal polyps or concomitant AR in patients with CRS did not show any differentiation in the results. Asthma was associated with significantly worse scores in all the psychometric questionnaires. Conclusion: Olfactory dysfunction was found to decrease QoL among patients. Anosmia, CRS disease, and asthma as clinical predictors were proved to be independently correlated with QoL, anxiety, and depression levels.